Determinant of Agricultural Cold Chain: Study Case Approach - Atong Soekirman (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The purpose of this research is to promote innovation in the development of technology and management solutions that can improve the overall performance of the cold chain. By identifying research gaps and lingering challenges in managing agricultural cold chains, this research aims to encourage the development of new and sustainable solutions that can improve operational efficiency, reduce waste, and improve product quality. This research is quantitative research by making observations to the respondent. The respondents who completed the questionnaire were farmers who use logistics services in Bekasi and its surroundings. Questionnaire questions are distributed directly to respondents. Data analysis in this study uses SPSS 25 by looking for the results of the influence between existing variables, namely independent and dependent variables. Harvest Handling and Electricity variables are not significant in influencing Cold Agriculture, while Cold Storage and Reefer Containers have a significant influence. Therefore, pay more attention to effective cold storage practices and integration of reefer containers in improving the quality and efficiency of agricultural cold chains. This could include improved cold storage infrastructure, the use of more advanced technology in reefer container management, and increased training for practitioners in equipment handling and use.